HASIL BELAJAR FISIKA DAN AKTIVITAS SISWA BERDASARKAN GENDER MELALUI PENERAPAN MODELPEMBELAJARAN KOLABORATIF PADA MATERI POKOK OPTIK DI KELAS X MA AL-IHSAN BOARDING SCHOOL KAMPAR. - Sahal, Muhammad; ', Fitrialisma; ', Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study was to describe the physics students achievement and describe the activities of students by gender with the implementation of collaborative learning model in MA Al Ihsan Boarding School Kampar. This research was conducted in class X MA Al Ihsan Boarding School Kampar from December 2014 through March 2015 by the research subjects consisted of 17 students in class of Ibnu Sina (boys) and 19 students in class of Al Khawarizmi (girls). The design of this study is the One Shot Case Study applied to two different classes. The research instrument is the form of sheet posttest and observation sheet to observe the activity of student activity during learning activities. Scores of achievement and student activity observation results were analyzed using descriptive analysis. Descriptive analyzes were conducted to determine the absorption, the effectiveness of teaching and learning activity levels between class boys and girls. The average score of student achievement girls was 50.11% (category quite good) and boys is 53.41% (category quite good). While the average score of student activity during the students learning is at high category with a score of 91.10 % for girls and 91.87 % for boys. Student achievement and learning activities of students in physics in boys is better than the achievement and learning activities of girls. So, it can conclude that by applying the collaborative learning model in boys is more effective than girls in the class X MA Al Ihsan Boarding School Kampar.Key Word : Achievement, Collaborative Learning, Gender, Student Activity.